2020
DOI: 10.1038/s41699-020-0141-3
|View full text |Cite|
|
Sign up to set email alerts
|

Discrete interactions between a few interlayer excitons trapped at a MoSe2–WSe2 heterointerface

Abstract: Inter-layer excitons (IXs) in hetero-bilayers of transition metal dichalcogenides (TMDs) represent an exciting emergent class of long-lived dipolar composite bosons in an atomically thin, near-ideal two-dimensional (2D) system. The long-range interactions that arise from the spatial separation of electrons and holes can give rise to novel quantum, as well as classical multi-particle correlation effects. Indeed, first indications of exciton condensation have been reported recently. In order to acquire a detaile… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 46 publications
3
55
1
Order By: Relevance
“…Further, the spatial mapping of the trapped IX positions indicates that, at the exceptionally low density of excitons that we optically generated, their position is essentially random: the moiré lattice is not discernible. We speculate that the particular site chosen by the exciton is likely determined by the local environment and perhaps aided by dipolar repulsion effects 31 , 32 .…”
Section: Mainmentioning
confidence: 98%
“…Further, the spatial mapping of the trapped IX positions indicates that, at the exceptionally low density of excitons that we optically generated, their position is essentially random: the moiré lattice is not discernible. We speculate that the particular site chosen by the exciton is likely determined by the local environment and perhaps aided by dipolar repulsion effects 31 , 32 .…”
Section: Mainmentioning
confidence: 98%
“…From the linear fit of the energy shift versus electric field, the dipole size or charge separation ( d ) has been estimated to be ~0.5–0.8 nm, matching well with the expected layer separation (~0.7 nm) 30 , 95 , 117 . Another consequence of the static electric dipole is the resulting dipole–dipole repulsive interactions between the interlayer excitons 22 , 28 , 30 , 118 , 119 , as revealed by a blue-shift in the PL energy with increasing exciton density (excitation power) (Fig. 3e ) 22 , 28 , 30 .…”
Section: Interlayer Exciton Formation In Tmd Vdw Heterostructuresmentioning
confidence: 99%
“…For example, TMDC bilayer heterostructures with twist-angle induces spatially periodic moiré superlattice potential that can trap IX, which has been predicted by several theoretical studies [23][24][25][26][27][28] and confirmed by a series of experiments [5,[29][30][31][32][33][34][35]. Strain has also been proposed as an effective way to trap IX, in which the band structures of TMDC heterostructures are modified by strain, resulting in the static potential well [16,[36][37][38]. The spatially varying electric fields enable the localization of IX due to its permanent dipole moment [10,39,40], where the deterministic placement and control of a single trapped IX has been achieved [39].…”
Section: Introductionmentioning
confidence: 99%